“Velocidad de infiltración del agua en el sub-suelo de Tamaute y Cubijíes, pertenecientes a los cantones Guano Riobamba, respectivamente, asociado a la granulometría y a la textura de sus componentes” - Flores Díaz, Katherine Isabe (2016)
In this research the different types of soils present in the subsoil of Tamaute and Cubijíes, belonging to the Guano and Riobamba cantons, respectively, were analyzed. These sites do not have a sewage system, so that the infiltration rates associated with the soil type were obtained, in order to design methods that replace it. The double cylinder infiltrameter method was adopted to obtain infiltration velocities, and particle size tests and Atterberg boundaries were used to classify soils with the AASHTO method. A total of 40 samples were analyzed corresponding to the above mentioned communities, of which the presence of 2 types of soil have been determined: A-3 (Fine sand) in 37.50% and A-2-4 (Gravel and clayey sand Silos) with 62.50%, with a clear predominance of soil type A-2-4. The infiltration velocity ranges for each type of soil have been determined: A3 (Fine sand) infiltration velocity fluctuates between 24.00 - 540.00 mm / h, for a soil of type A-2-4 (Gravel and Sands) the value fluctuates between 36.00 - 180.00 mm/h.